2021
DOI: 10.1108/k-10-2020-0671
|View full text |Cite
|
Sign up to set email alerts
|

Virtual medical learning: a comprehensive study on the role of new technologies

Abstract: PurposeHealthcare employs informatics to offer its services through information technology where the social network can aid virtual medical learning. Since the usage of the internet and other electronic tools for medical services delivery is at the initial stage, it is essential to examine the factors that condition patients and medical elements in a virtual environment can develop relationship models on the health services. So, the authors have systematically reviewed virtual medical learning and offered some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
(65 reference statements)
1
4
0
Order By: Relevance
“…In accordance with other research, interacting with gamification has helped participants to connect through simulation and virtual reality, thanks to the fun aspect with respect to previous activities, developing creativity, collaboration and development skills (Baxter and Hainey, 2020;C ozar-Guti errez and S aez-L opez, 2016;Llorens-Largo et al, 2016). Increased motivation has also been demonstrated (Alsawaier, 2018;Barata et al, 2013;Buckley et al, 2014;Charles et al, 2011;Tang et al, 2022) as well as the incentive to participate (Jo et al, 2018;S anchez-Mart ın et al, 2017;Zainuddin et al, 2020), leading to great advances in more dynamic classes, with access to immediate material and increased contact with the teacher compared to traditional learning.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…In accordance with other research, interacting with gamification has helped participants to connect through simulation and virtual reality, thanks to the fun aspect with respect to previous activities, developing creativity, collaboration and development skills (Baxter and Hainey, 2020;C ozar-Guti errez and S aez-L opez, 2016;Llorens-Largo et al, 2016). Increased motivation has also been demonstrated (Alsawaier, 2018;Barata et al, 2013;Buckley et al, 2014;Charles et al, 2011;Tang et al, 2022) as well as the incentive to participate (Jo et al, 2018;S anchez-Mart ın et al, 2017;Zainuddin et al, 2020), leading to great advances in more dynamic classes, with access to immediate material and increased contact with the teacher compared to traditional learning.…”
Section: Discussionsupporting
confidence: 73%
“…The new methodology implemented with the obvious help of new technologies such as virtual reality and simulation means that, through participation, participants gain two important advantages. On the one hand, and most notably, it makes the learning process easier compared to traditional learning and, on the other hand, increased teamwork (Beh et al, 2022;Garc ıa et al, 2016), in addition to encouraging participation, increasing interactions and the openness of participants (Sandahl et al, 2013;Tang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tang et al [22] offered insights into the impact of new technologies, particularly within the context of virtual medical learning. Their systematic review showed how informatics and virtual platforms are revolutionizing medical education and training, thereby enhancing the delivery and accessibility of medical services and education within virtual settings.…”
Section: -Introductionmentioning
confidence: 99%